SEJARAH PERKEMBANGAN PONDOK PESANTREN DAR AHLUSSUNNAH WALJAMA’AH DI KECAMATAN KUBU TAHUN 1999-2012 - jannah, Fattahul; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Islamic boarding schools have been known in Indonesia since the days of Walisongo. At that time Sunan Ampel established a hermitage in Ampel Surabaya and made it an educational center in Java. The students who came from Java came to study religion. Even among the students who want to study there are those from Gowa, Talo and Sulawesi. The objectives of this study are: (1) To find out the background of the establishment of the Dar Aswaja Islamic boarding school. (2) To find out the development of Dar Aswaja Islamic boarding school in 1999-2012. (3) To find out how the community responded to the Dar Aswaja boarding school. The method used in this research is qualitative method. Data obtained from the results of the interview are then analyzed in their own language. The research location is Sungai Pinang Village, Kubu District, Rokan Hilir Regency. Research time starts after the seminar proposal until the thesis examination. Data collection techniques used were interview techniques, and documentation techniques. The results of this study indicate that the Dar Aswaja Islamic Boarding School was established in 1989, the acceptance of the first santri or students was conducted in 1997 and ratified in 1999 which was pioneered by KH. Syaufi He had the idea to form an Islamic Boarding School educational institution that aims to educate the whole community, especially for the Kubu District so that the students would become useful for themselves, for the homeland and the nation.Key Words: History of Development of Dar Aswaja Islamic Boarding School